2013
DOI: 10.1074/jbc.m113.498329
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates in the Guanine Nucleotide Exchange Reaction of Rab8 Protein Catalyzed by Guanine Nucleotide Exchange Factors Rabin8 and GRAB

Abstract: Background:The GEFs Rabin8 and GRAB are activators of the vesicular trafficking regulator Rab8. Results: The catalytic mechanism of Rabin8/GRAB in Rab8 has been elucidated in biophysical and structural detail. Conclusion: Rabin8 and GRAB are catalytically moderately efficient enzymes and act by disturbing Mg 2ϩ binding and Rab8-guanine base interactions. Significance: Obtaining snapshots of the nucleotide exchange reaction is crucial to understanding the mechanism of Rab GEFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 42 publications
(54 reference statements)
7
93
0
Order By: Relevance
“…Studies in the yeast secretory pathway have shown that Rab GTPases can be sequentially activated via GEF/effector complexes (Ortiz et al 2002). A subset of GEFs could be identified via bioinformatics approaches based on the presence of a conserved DENN domain (Yoshimura et al 2010;Wu et al 2011); however, there are GEF family members that are structurally distinct (Esters et al 2001;Guo et al 2013). Clearly, more factors such as GEFs, GAPs, and effectors coupling the activities of individual and sequentially acting Rab proteins need to be identified and characterized to fully understand how cargo flows between compartments on the endocytic pathway and endocytosis is coordinately up-regulated to address physiological demands.…”
Section: Rab Gtpases On the Endocytic Pathway Compartmentalize Endocymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the yeast secretory pathway have shown that Rab GTPases can be sequentially activated via GEF/effector complexes (Ortiz et al 2002). A subset of GEFs could be identified via bioinformatics approaches based on the presence of a conserved DENN domain (Yoshimura et al 2010;Wu et al 2011); however, there are GEF family members that are structurally distinct (Esters et al 2001;Guo et al 2013). Clearly, more factors such as GEFs, GAPs, and effectors coupling the activities of individual and sequentially acting Rab proteins need to be identified and characterized to fully understand how cargo flows between compartments on the endocytic pathway and endocytosis is coordinately up-regulated to address physiological demands.…”
Section: Rab Gtpases On the Endocytic Pathway Compartmentalize Endocymentioning
confidence: 99%
“…First, Rab GTPases undergo cycles of GTP binding and hydrolysis to GDP, which serves to drive a reversible conformational change that is decoded by interacting proteins (Wittinghofer et al 1993). Guanine-nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) catalyze the exchange and hydrolysis reactions and, therefore, act as regulators of the GTP-GDP cycle (Yoshimura et al 2010;Wu et al 2011;Barr 2013;Guo et al 2013;Kotting and Gerwert 2013). Second, Rab GTPases behave both as soluble and specifically localized, integral-membrane proteins.…”
mentioning
confidence: 99%
“…The interaction between a nucleotide-free Rab and a GEF, which is an intermediate step in the activation process, is usually stable, and thus allows their crystal structures to be determined. Thus far, at least five crystal structures of Rab-GEF complexes, i.e., of Rabex5-Rab21, Sec2p-Sec4p, Rabin8-Rab8, TRAPP I-Ypt1p, and DENND1B-Rab35, have been determined, and they provide the structural basis for Rab activation by these GEFs (Delprato and Lambright, 2007;Dong et al, 2007;Sato et al, 2007;Cai et al, 2008b;Wu et al, 2011;Guo et al, 2013). The stable interaction between GEFs and their substrate Rabs can be applied to identifying the substrate specificity of GEFs, e.g., the Rab21-specific GEF Varp specifically interacts with a constitutively negative form of Rab21 and does not interact with constitutively negative forms of 59 other Rabs (Tamura et al, 2009;Mori et al, 2013).…”
Section: Principles Of the Gef-accelerated Gdp-gtp Exchange Reactionmentioning
confidence: 99%
“…It is therefore possible that such uncharacterized longin proteins (e.g., DENN-related protein; see next section) function as In general, a GDP-bound form of Rab is present in the cytosol through interaction with GDI (top). A GEF, a Rab activation enzyme, forms a high-affinity complex with a nucleotide-free form of the Rab (bottom right), and such complexes are often used for crystallographic analysis because of their stability (Delprato and Lambright, 2007;Dong et al, 2007;Sato et al, 2007;Cai et al, 2008b;Wu et al, 2011;Guo et al, 2013). When the Rab binds to GTP, the GEF is released from the Rab (bottom left).…”
Section: Substrates and Functions Of Rab-gefsmentioning
confidence: 99%
See 1 more Smart Citation